Espiritualidade não religiosa na escola: meditação e cuidado de si na ótica de Michel Foucault - Silva, Renata Tatianne de Lima (2023)
This work sought to investigate the theme of meditation by searching for the possible experience of religious education teachers in the city of Bayeux in the state of Paraíba. The aim was to investigate the use or non-use of meditative practices among these teachers, using the secular nature of the practice as a parameter. For this, qualitative research and sociometric data analysis were carried out. To this end, the theoretical basis explored to address the topic of meditation was the philosopher Michel Foucault's concept of "selfcare". From this, a questionnaire was applied to teachers approved by Plataforma Brazil under opinion: 5.777.109. The questionnaire aimed to understand the possibilities of experiences and acceptance in relation to meditative practices and how these practices had or did not influence the fight against stress arising from work activities in the school environment at the time of the Covid 2019 pandemic among this public. According to bibliographical research, meditation has been recognized and practiced as a tool capable of helping to promote health and well-being by combating stressors by various professionals, including those in education, and, therefore, extending the benefits obtained to their work environments. In some public schools in Brazil, for example, meditation has been gradually introduced by teachers from different areas. However, the objective of the present work was to investigate the possibility of initiatives and results derived from the practice of meditation in the expectations of religious education teachers in Bayeux. By using Michel Foucault's philosophical approach, the idea of searching for self-knowledge through selfcare linked to self-care through the practice of meditation was reinforced, as this valuable tool can and should be explored beyond the spiritual sense as well as in a secular way. in public or private environments. Finally, this research was focused on the temporal context of the COVID 19 Pandemic, where remote teaching prevailed with all the challenges that this period offered to teachers.